THE EFFECT OF TIME DISCIPLINE ON THE ACHIEVEMENT OF TAHFIZH'S TARGET IN THE FINAL SEMESTER (Case Study of Student IIQ Jakarta Faculty of Tarbiyah Study Program PAI Class of 2017) - Siti Khaulah Nadhiroh; Adithiya Warman (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
The background of this research is the disciplinary event when students achieve their tahfizh target in the final semester. This study aims to determine the effect of time discipline on the achievement of the tahfizh target in the final semester of IIQ Jakarta Students, Faculty of Tarbiyah, Islamic Studies Study Program Class 2017. This study uses a descriptive quantitative approach, and uses a survey method. The population of this study were students of the Tarbiyah Faculty of Islamic Studies Study Program class of 2017, totaling 115 people. Data collection techniques using observation, interviews and questionnaires. The instrument validity test used Product Moment correlation, and the reliability test used Cronbach's Alpha formula with a total of 89 students as respondents. The analysis assumption test consists of normality test, linearity test and heteroscedasticity test. The hypothesis test of this research is simple linear regression. The results of this study indicate that time discipline has a high enough influence on the achievement of the tahfizh target with a result of 49.9% and the remaining 50.1% is influenced by other factors not examined by the author. Penelitian ini di latar belakangi oleh peristiwa kedisiplinan waktu mahasiswa dalam pencampaian target tahfizhnya di semester akhir. Penelitian ini bertujuan untuk mengetahui pengaruh kedisiplinan waktu terhadap pencapaian target tahfizh di semester akhir pada Mahasiswi IIQ Jakarta Fakultas Tarbiyah prodi PAI Angkatan 2017. Penelitian ini menggunakan pendekatan kuantitatif deskriptif, dan memakai metode survei. Populasi dari penelitian ini adalah mahasiswi Fakultas Tarbiyah Prodi PAI angkatan 2017 yang berjumlah 115 orang. Teknik pengumpulan data menggunakan observasi, wawancara dan kuesioner. Uji validitas instrumen menggunakan korelasi Product Moment, dan uji reliabilitas mengunakan rumus Alpha Cronbach’s dengan jumlah responden sejumlah 89 mahasiswa. Uji asumsi analisis ini terdiri dari uji normalitas, uji linearitas dan uji heteroskedastisitas. Uji hipotesis penelitian ini adalah regresi linier sederhana. Hasil penelitian ini menunjukkan bahwa kedisiplinan waktu memiliki pengaruh yang cukup tinggi terhadap pencapaian target tahfizh dengan hasil sebesar 49,9% dan selebihnya yang berjumlah sebesar 50,1% dipengaruhi oleh faktor lain yang tidak diteliti oleh penulis.